Oxidative Stress Markers and C-Reactive Protein Are Related to Severity of Heart Failure in Patients with Dilated Cardiomyopathy - Wojciechowska, Celina; Romuk, Ewa; Tomasik, Andrzej; Skrzep-Poloczek, Bronisława; Nowalany-Kozielska, Ewa; Birkner, Ewa; Jacheć, Wojciech (Mediators of Inflammation, 2014)
Background. The aim of study was to determine relationships between functional capacity (NYHA class), left ventricle ejection fraction (LVEF), hemodynamic parameters, and biomarkers of redox state and inflammation in patients with dilated cardiomyopathy (DCM). Methods. DCM patients (n=109, aged 45.97±10.82 years), NYHA class IIV, and LVEF 2.94±7.1% were studied. Controls comprised age-matched healthy volunteers (n=28). Echocardiography and right heart catheterization were performed. Serum activities of superoxide dismutase isoenzymes (MnSOD and CuZnSOD), concentrations of uric acid (UA), malondialdehyde (MDA), and C-reactive protein (hs-CRP) were measured. Results. MnSOD, UA, hs-CRP, and MDA were significantly higher in DCM patients compared to controls. Except MDA concentration, above parameters were higher in patients in III-IV NYHA class or with lower LVEF. hsCRP correlated with of MnSOD (P<0.05) and CuZnSOD activity (P<0.01). Both isoenzymes positively correlated with mPAP and pulmonary capillary wedge pressure (MnSOD, resp., P<0.01 and P<0.05 and CuZnSOD P<0.05; P<0.05). UA positively correlated with MnSOD (P<0.05), mPAP (P<0.05), and PVRI (P<0.05). The negative correlation between LVEF and UA (P<0.01) was detected. Conclusion. There are relationships among the severity of symptoms of heart failure, echocardiographic hemodynamic parameters, oxidative stress, and inflammatory activation. Increased MnSOD activity indicates the mitochondrial source of ROS in patients with advanced heart failure.